Mitigation of bacterial adhesion on metal surfaces by surface roughness modification - Noratiqah, Chik (2021)
Bio-fouling caused by bacterial adhesion on metal surfaces creates contamination in medical equipment, bio-corrosion of industrial devices and many more. Bacterial adhesion on a surface will develop a biofilm which will be extremely difficult to remove. Therefore, industries had suffered from billions of dollars for the process of removing and cleaning the biofilm. Many factors that contributed to the bacterial adhesion had been studied but factors related to the surface topography are found inconsistence and not accurate. Hence, this study was investigating on the effect of surface topography towards bacterial adhesion. The objectives of this study are to evaluate the effect of varying surface properties towards the bacterial adhesion on the metal surfaces which also will be associated with other factors like bacterial properties and environmental factors. Escherichia coli (E. coli) ATCC 8739 and Staphylococcus aureus (S. aureus) ATCC 6838 were used in the adhesion test on stainless steel AISI 316L (SS) and Grade 5 titanium alloys (TT) where the test has been carried out for 4 hours for each process. SS and TT surfaces were fabricated by using the polishing technique (P-control), grinding (G), millisecond laser (Ml) and ultrafast laser (Ul). The characterizations of the metal and bacterial surfaces have been investigated. Ul surfaces are mainly hydrophobic while G and Ml surfaces are mostly hydrophilic. In terms of surface roughness, G, Ml and Ul techniques had produced Sq (root mean square roughness) ranging from 98.34 nm – 720 nm for SS and 88.92 nm – 630 nm for TT, while CAM (Contact angle measurement) for the surfaces varies between 70° to 146°. E. coli ATCC 8739 was reported to have a hydrophilic surface while S. aureus ATCC 6838 has a hydrophobic surface and both have negative surface charge. Based on the effect of pH and salt concentration towards the bacterial adhesion, the results showed that when pH increased the number of bacterial adhered on P-SS and P-TT had reduced about 44% - 75% while the increase of salt concentration had increased up to 10-fold of adhesion of both bacteria. This is because the changes of pH and salt concentration of bacterial solution had influenced the bacterial surface charge and the ionic strength thus, affecting the adhesion. Besides that, Ul surfaces were found to have the lowest adhesion of E. coli ATCC 8739 and S. aureus ATCC 6838 on both Ul-SS and Ul-TT which is about 12% to 98% of reduction when compared to P surface (control). Ul also had proved can reduce E. coli ATCC 8739 adhesion on both SS and TT with a 10% - 91% of reduction when compared to G and Ml surfaces. The generation of LIPSS (ripples) and nano-sized irregular grains on the Ul surfaces after the fabrication process had contributed to the bacterial reduction by minimizing the contact point between the bacteria and metal surfaces. Overall, the highest reduction for E. coli ATCC 8739 (20% - 98%) and S. aureus ATCC 6838 (12% - 78%) against polished surface was achieved with Ul specifically at Ul-SS-0.10 with Sq = 298 nm and Sds = 17039.43/mm2 and Ul-TT-0.10 with Sq = 210 nm and Sds = 16456.30/mm2 which were mainly contributed due to the increase of hydrophobicity and roughness.